Enhanced Growth of Multipurpose Calliandra (Calliandra calothyrsus) Using Arbuscular Mycorrhiza Fungi in Uganda. (17th December 2012) - Sebuliba, Esther; Nyeko, Phillip; Majaliwa, Mwanjalolo; Eilu, Gerald; Kizza, Charles Luswata; Ekwamu, Adipala
Abstract : This study was conducted to compare the effect of selected arbuscular mycorrhiza fungi genera and their application rates for enhanced Calliandra growth in Uganda. The performance of Calliandra under different types and rates of arbuscular mycorrhiza fungi inoculation was assessed in the greenhouse using sterilized Mabira soils. Four dominant genera were isolated from the rhizosphere of sorghum in the laboratory. Calliandra seeds were grown in pots and the seed coating method of application was used at concentrations of 0 spores, 30 spores and 50 spores. Each treatment was replicated three times. All Calliandra inoculated seedlings showed improved seedling growth (in terms of height and shoot dry matter weight) compared to the control (P < 0.05 ) except with the arbuscular mycorrhiza fungi mixture treated Calliandra at 50 spores rate. Glomus sp. and Acaulospora sp. had significant influence on the height of Calliandra, while AMF mixture performed best in terms of shoot dry weight (P < 0.05 ). This study provides a good scope for commercially utilizing the efficient strains of arbuscular mycorrhiza fungi for beneficial effects in the primary establishment of slow growing seedlings ensuring better survival and improved growth.